2015
DOI: 10.1111/1365-2745.12427
|View full text |Cite
|
Sign up to set email alerts
|

Termites amplify the effects of wood traits on decomposition rates among multiple bamboo and dicot woody species

Abstract: Summary1. Wood decomposition is a key process in the terrestrial carbon cycle, controlling carbon storage with feedback to climate. In (sub) tropical forest, termites are major players in wood decomposition, but their role relative to that of microbial decomposers and wood traits of different tree species is poorly understood. The current literature also has strong bias towards dicot tree decomposition, while abundant woody monocots, particularly bamboos, also contribute greatly to (sub) tropical carbon cyclin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
42
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 43 publications
(56 citation statements)
references
References 66 publications
2
42
2
Order By: Relevance
“…Indeed, the mesofaunal contribution was strongly regulated by litter traits, being higher in nutrient‐rich and less lignified litter than in recalcitrant litter across elevations (Figure a). This finding supports some previous empirical evidence for the mesofaunal contribution (Fujii et al., ; Schädler & Brandl, ) and shows an analogy with the contribution of (meso‐ and) macrofauna to decomposition (Coq, Souquet, Meudec, Cheynier, & Hattenschwiler, ; Garcia‐Palacios et al., ; Liu et al., ). However, other papers reported a greater role for mesofauna in more recalcitrant litter or nutrient‐poorer sites (Milcu & Manning, ; Perez et al., ; Yang & Chen, ).…”
Section: Discussionsupporting
confidence: 91%
“…Indeed, the mesofaunal contribution was strongly regulated by litter traits, being higher in nutrient‐rich and less lignified litter than in recalcitrant litter across elevations (Figure a). This finding supports some previous empirical evidence for the mesofaunal contribution (Fujii et al., ; Schädler & Brandl, ) and shows an analogy with the contribution of (meso‐ and) macrofauna to decomposition (Coq, Souquet, Meudec, Cheynier, & Hattenschwiler, ; Garcia‐Palacios et al., ; Liu et al., ). However, other papers reported a greater role for mesofauna in more recalcitrant litter or nutrient‐poorer sites (Milcu & Manning, ; Perez et al., ; Yang & Chen, ).…”
Section: Discussionsupporting
confidence: 91%
“…Our results show that macro-invertebrates have little effect on wood decay, while microbial decomposers are the main agents of decay during the observed period. This finding contradicts recent studies from subtropical forests that found significantly lower decay rates of wood and bamboo in subtropical forests when termites were excluded (Liu et al 2015, Eichenberg et al 2017. However, both studies were conducted in forest communities with far lower leaf area index and a more open canopy structure than our system.…”
Section: No Effect Of Macro-invertebrate Exclusion On Wood Mass Loss contrasting
confidence: 99%
“…These results are in accordance with the findings of Liu et al (2015), who reported the role of termites in enhancing the effect of wood traits on decomposition. Moreover, root foraging occurs more on dead wood hollowed by termites, thereby, accelerating nutrient cycling (Lu et al, 2013).…”
Section: Discussionsupporting
confidence: 93%